Fatigue endurance and leakage characteristics of ferroelectric BaBiO₃ thin films obtained by the polymeric precursor method - Acero, G. [UNESP] (2025)
This study describes a straightforward synthesis route for producing barium bismuthate (BaBiO3) thin films via the polymeric precursor method. The research investigates the temperature-dependent characteristics of fatigue resistance and leakage behavior. The findings emphasize the crucial role of annealing temperature in influencing crystallization, morphology, fatigue resistance, and leakage current. Morphological analysis reveals distinct film structures influenced by annealing temperature. Specifically, the film annealed at 600°C exhibits higher remnant polarization (19.87 μC/cm2) compared to the film annealed at 800°C (8.41 μC/cm2). This behavior can be attributed to the small grain size, which enhances boundary effects and the contributions of domain walls. The 800°C annealed film exhibits a plate-like grain structure, with leakage current characteristics consistent with the traps-filled limit voltage (VTFL)-mechanism. In contrast, the film annealed at 600°C displays rounded grains and its high-field conduction behavior is well described by the space-charge-limited conduction (SCL) mechanism. Furthermore, the film annealed at 600°C demonstrates better fatigue resistance, sustaining up to 108 switching cycles without degradation. These results position it as a promising candidate for actuators, switches, and emerging electronic memory device applications. In conclusion, this study highlights the significance of annealing temperature in tailoring the properties of BaBiO3 thin films, providing valuable insights for optimizing their performance across various technological applications.